Quantifying Institutional Impacts and Development Synergies in Water Resource Programs : A Methodology with Application to the Kala Oya Basin, Sri Lanka - Saleth, R. Maria; Dinar, Ariel (World Bank, Washington, DC, 2012)
The success of development programs, including water resource projects, depends on two key factors: the role of underlying institutions and the impact synergies from other closely related programs. Existing methodologies have limitations in accounting for these critical factors. This paper fills this gap by developing a methodology, which quantifies both the roles that institutions play in impact generation and the extent of impact synergies that flows from closely related programs within a unified framework. The methodology is applied to the Kala Oya Basin in Sri Lanka in order to evaluate the impacts of three water-related programs and the roles of 11 institutions in the context of food security. The results provide considerable insights on the relative role of institutions and the flow of development synergies both within and across different impact pathways. The methodology can also be used to locate slack in impact chains and identify policy options to enhance the impact flows.